Selection of Branded Alcoholic Beverages by Underage Drinkers - Ross, Craig S. (J Adolesc Health, 2015)
PURPOSE: To identify reasons why youth choose to drink specific brands of alcohol and to determine if these reasons are associated with problem drinking patterns and outcomes. METHODS: We conducted an Internet survey of 1,031 youth ages 13 to 20 who reported drinking within the past 30 days. Of these, 541 youth who reported having a choice of multiple brands of alcohol the last time they drank stated (yes/no) whether each of 16 different reasons had influenced their choice of a specific brand. We reduced these 16 reasons to three principle components and used Latent Class Modeling to identify five groups of youth with similar reasons for selecting a brand, which we then profiled. RESULTS: We grouped respondents into the following brand selection groups: “Brand Ambassadors” who were distinguished from other clusters by selecting a brand because they identified with it (32.5% of respondents), “Tasters” who selected a brand because they expected it to taste good (27.2%), “Bargain Hunters” who selected a brand because it was inexpensive (18.5%), “Copycats” who selected a brand because they’d seen adults drinking it or seen it consumed in movies or other media (10.4%), and “Others” (11.5%). Brand Ambassadors and Copycats reported the largest amount of alcohol consumed and had the greatest prevalence of both heavy episodic drinking and negative alcohol-related health consequences. CONCLUSIONS: Underage drinkers who cite marketing influences and adult or media modeling of brand choices as their reasons for selecting alcohol brands are likely to drink more and incur adverse consequences from drinking.